Pendampingan Pembuatan Akun Marketplace Digital dan Design Kemasan Serta Logo Bagi UMKM Terdampak Pandemi Di Kota Pekanbaru - Kornita, Sri Endang; Sefaren, Sefaren; Isbah, Ufira; Utami, Bunga Chinta; Misdawita, Misdawita (Journal of Community Engagement Research for Sustainability, 2023)
Many of the MSME actors in the food industry and businesses that have been impacted by the COVID-19 epidemic are still very small businesses with very basic financing, product production, marketing, and product standardization capabilities.. Based on the identification of the problems faced by MSME actors, it is known that product packaging has not been designed properly, as well as the need to maintain and develop its business to be more advanced in order to develop its business activities properly, and be able to increase MSME income, so steps and strategies are needed for business development. based on the conditions and problems encountered. The method of application carried out in this service was mentoring MSMEs who are members of the Riau Food Association organization that persist in carrying out business activities during this pandemic in branding and packaging as well as digital/online marketing of products to improve product quality. In the implementation of this service, the service team also assists MSMEs in online marketing to business actors through marketplace and social media. The results of this service activity showed that MSMEs gained knowledge of business management, engaged in online marketing, had packaging with business brands, and were better able to maintain their operations and grow their income during the pandemic than they had been before taking part in service activities.